Combat biofouling with microscopic ridge-like surface morphology: a bioinspired study - Fu, Jimin; Zhang, Hua; Guo, Zhenbin; Feng, Dan-qing; Thiyagarajan, Vengatesen; Yao, Haimin (Journal of the Royal Society interface, 2018)
Biofouling refers to the unfavourable attachment and accumulation of marine sessile organisms (e.g. barnacles, mussels and tubeworms) on the solid surfaces immerged in ocean. The enormous economic loss caused by biofouling in combination with the severe environmental impacts induced by the current antifouling approaches entails the development of novel antifouling strategies with least environmental impact. Inspired by the superior antifouling performance of the leaves of mangrove tree Sonneratia apetala, here we propose to combat biofouling by using a surface with microscopic ridge-like morphology. Settlement tests with tubeworm larvae on polymeric replicas of S. apetala leaves confirm that the microscopic ridge-like surface morphology can effectively prevent biofouling. A contact mechanics-based model is then established to quantify the dependence of tubeworm settlement on the structural features of the microscopic ridge-like morphology, giving rise to theoretical guidelines to optimize the morphology for better antifouling performance. Under the direction of the obtained guidelines, a synthetic surface with microscopic ridge-like morphology is developed, exhibiting antifouling performance comparable to that of the S. apetala replica. Our results not only reveal the underlying mechanism accounting for the superior antifouling property of the S. apetala leaves, but also provide applicable guidance for the development of synthetic antifouling surfaces.